PENERAPAN PENDEKATAN ETNOPEDAGOGI BERBASIS LINGKUNGAN DALAM PEMBELAJARAN KETERAMPILAN MENULIS TEKS PUISI SISWA KELAS X SMA NEGERI 1 TANJUNG MUTIARA KABUPATEN AGAM - Astry Wulandari; Zulfikarni; Andria Catri Tamsin; Nofrahadi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The purpose of this study is to describe the implementation of an environment-based ethnopedagogical approach in teaching poetry writing skills to tenth-grade students at SMA Negeri 1 Tanjung Mutiara, Agam Regency. This study employed a descriptive qualitative method. Data were collected through observation, interviews, and documentation involving Indonesian language teachers and students as informants. The results indicate that the implementation of the environment-based ethnopedagogical approach consists of three main stages: planning, implementation, and evaluation. In the planning stage, the teacher designed learning tools by integrating local cultural values and environmental elements. In the implementation stage, students actively engaged in observing the school environment to generate ideas for writing poetry. In the evaluation stage, students’ works were assessed based on diction, imagery, creativity, and the integration of cultural and environmental values. The findings demonstrate that this approach enhances students’ creativity, engagement, and ability to express ideas in poetic form, while also fostering cultural awareness and environmental sensitivity.